2019
DOI: 10.3390/ijms20010219
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Affects Mouse Sperm Parameters, Spontaneous Acrosome Reaction, and Fertility Capacity

Abstract: Leukemia is one of the most common cancers in patients of reproductive age. It is well known that chemotherapy, used as anti-cancer therapy, adversely affects male fertility. Moreover, the negative effect of leukemia on sperm quality, even before chemotherapy treatment, has been reported. However, the mechanisms behind this disease’s effect on sperm quality remains unknown. In this study, we examine the direct effect of leukemia and chemotherapy alone and in combination on sperm parameters and male fertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Sperm cells were extracted from the tail of the epididymis by squeezing in a Petri dish plate. Collected sperm from all examined groups of treated mice were examined for concentration and motility using a Makler counting chamber, as described previously [ 18 ]. Evaluation of sperm morphology was performed according to the WHO criteria [ 55 ], and as described previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm cells were extracted from the tail of the epididymis by squeezing in a Petri dish plate. Collected sperm from all examined groups of treated mice were examined for concentration and motility using a Makler counting chamber, as described previously [ 18 ]. Evaluation of sperm morphology was performed according to the WHO criteria [ 55 ], and as described previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the precise mechanism has not yet been totally clarified, poor semen quality in these patients may be a result of endocrine/paracrine disturbances, systemic effects of cancer, or both [ 15 , 16 , 17 ]. Recently, we used an AML adult mice model and showed a significant reduction in testes weight, sperm parameters and fertility within weeks post injection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that different types of cancers, including leukemia, lymphoma, testicular cancer, non-Hodgkin's disease, gastrointestinal malignancy, and musculoskeletal malignancy, affect sperm parameters and the quality of thawed cryopreserved sperm [7,8]. Recently, using a mature animal model of leukemia, we showed that acute myeloid leukemia (AML) significantly decreased sperm parameters, increased spontaneous acrosome reaction, and decreased both male fertility capacity and number of offspring [9]. Thus, cancer may lead to male subfertility/infertility.…”
Section: Cancer and Male Infertilitymentioning
confidence: 99%
“…In-vitro culture: Differentiation to SSCs 8,9 Intercourse or ART Fertility restoration (8) Needs more research for validation, safety, efficiency, and genetic stability (9) Not yet applicable in humans Differentiation of SSCs to sperm 8,9 ART…”
Section: Artmentioning
confidence: 99%
“…This study showed that the ejaculate modified gene expression in the endometrium and oviduct, and this was dependent on the sperm fraction considered. The effect of leukemia in sperm biology was studied in a murine model [4], showing that leukemia altered spermatozoa, increasing the spontaneous acrosome reaction, and decreasing the number of pups born. Ethanol is one of the major concerns in public health and is directly linked to numerous forms of cancer and mental problems.…”
mentioning
confidence: 99%